A Strategic Approach to Business Transformation for Achieving Sustainable Corporate Performance - Harianto, Frans B. M. Dabukke,; Djohar, Bungaran Saragih, Setiadi (Journal of Ecohumanism, 2024)
This study analyzes the Business Transformation Strategy for achieving sustainable corporate performance at PT Pupuk Indonesia (Tbk) using the Analytical Hierarchy Process (AHP). Key factors, actors, objectives, and strategic alternatives were identified to determine the most critical components driving the company’s transformation. Governance emerged as the top priority factor, emphasizing the importance of robust governance structures in ensuring transparency and accountability. The Directors were found to be the most influential actors, underscoring the need for strong leadership in steering the transformation process. Improving operational efficiency was ranked as the highest priority objective, reflecting the company’s focus on optimizing processes and enhancing productivity. The most important strategic alternative identified was the implementation of best practices in operational management, particularly through methodologies such as Lean and Six Sigma. The study concludes that effective governance, leadership involvement, operational efficiency, and the adoption of industry best practices are key to PT Pupuk Indonesia’s successful business transformation and long-term sustainability.